Self-Care Ability of the Elderly and Related Factors - Sepehr Noohi; Farzaneh Karamitanha; Alireza Shoghli (Zanjan University of Medical Sciences and Health Services, 2022)
Background: Self-care ability is a determinant factor in managing the daily lives of the elderly. Objectives: This study aimed to investigate self-care ability in the elderly and related factors. Methods: In this cross-sectional study, elderly people admitted to educational and medical hospitals in Zanjan in 2021 were selected by convenience sampling and 175 people over 60 years old evaluated with questionnaire including demographic information and self-care ability scale for elderly. Mean (standard deviation), frequency (percentage) and independent sample t-test were used to analyze data in SPSS 23. Results: The mean (SD) score of elderly self-care in this study was 53.86 (1.41). The results showed that self-care ability is low in most participants (68%). Women have significantly higher self-care ability than men (P=0.018). With increased age, Self-care ability decreased (P=0.0001). In illiterate and lower educated people, self-care ability is significantly lower (P=0.0001), and also rural residents have significantly less self-care ability than urban residents (P=0.0001). Elderly people who were married (P=0.0001) and had a source of income (P=0.0001) had a better level of self-care. Conclusion: Self-care ability is low in most elderly people, and self-care ability is worse in men, illiterate people, and villagers and self-care ability decreases with increasing age. It is suggested that simple programs be developed according to the age and level of literacy of the elderly.